IMPLEMENTASI KONSEP DESAIN PARTISIPASI PADA INTERIOR RUANG TERAPI PERILAKU ANAK AUTIS DENGAN MENGGUNAKAN METODA ABA/LOVASS - Sari, Sriti Mayang (Dimensi Interior, 2011)
The concept of participation design in the interior of a therapy room for autistic behavior in children truly considers the character of children with autism and methods of therapy used so that the criteria and the embodiment of space can meet the demands of autistic children. The physical environment that is suitable with the condition of the user can bring great influence to the therapy activities. The purpose of this research is to implement the design concept of participation as the basis in designing the interior of the therapy room for autistic children. The concept of participation design is implemented in the furniture arrangement, space-forming elements and the furniture.